Relation between CYP17 Polymorphism and Hyperandrogenemia in Polycystic Ovarian Syndrome - Budi Wiweko (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objectives: To find 5-untranslated region polymorphism of CYP17 gene and its connection with hyperandrogenemia in polycystic ovarian syndrome. Methods: A cross sectional descriptive study with consecutive random sampling method. Body mass index, ovarian morphology by ultrasonography, fasting insulin level, fasting blood glucose level, 17-hydroxyprogesterone level, total testosterone level, serum hormone binding globulin level, and CYP17 gene polymorphism in 45 subject with PCOs and 45 control subject who attend Yasmin clinic of Cipto Mangunkusumo General Hospital with menstruation problems were measured. CYP17 gene polymorphism was evaluated using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method with MspA1 restriction enzyme. Results: In PCOs group, the genotype distribution were; 11.1% subject with genotype CC, 71.1% subject with genotype TC and 17.8% subject was wild type TT. In non PCOs group, the genotype distribution for CC, TC and TT respectively were 13.3%, 46.7% and 40%. There was significant difference between both group in distribution of TC and TT genotype, with p value 0.013. Frequencies of allele c and allele t in PCOs group were 47% and 53%. In non PCOs group, frequency of allele c and t were 37% and 63%. There were tendency for higher frequency of allele c in the PCOs group but the difference was not statistically significant. Median FAI value for genotype CC homozygote, TC heterozygote and TT homozygote in PCOs group respectively were; 6.82 (6.07 - 8.23); 5.59 (0.25 -21.45) and 4.74 (3.48 - 8.88). There was tendency for increase FAI value in PCOs group corresponds to variant allele, but the result was not statistically different. Conclusion: There were higher proportion of CC homozygote and TC heterozygote genotype in PCOs patient with tendency of increasing FAI value. [Indones J Obstet Gynecol 2011; 35-1: 3-7] Keyword: polycystic ovarian syndrome, free androgen index, CYP17 polymorphism